1980
DOI: 10.1002/anie.198004651
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decarboxylation of β‐Lactones: Steric Hindrance of Mesomerism as Indication of a Zwitterionic Intermediate

Abstract: ET ["I and 815f.61 the refractive index n and its functions yield the best correlations, saving the tetrachloromethane values. With ( 1 -l/n2), the solvent-dependent term of an energy parameter'5'', one obtains the relationships (10) to (12) (valid at 20 "C): -Karlstr. 23,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…In view of the fact that thiolates are well-known to open β-lactones by S N 2 attack at the β-position, this remarkable reaction might be viewed as an intramolecular S N 2-like process involving a bicyclo[2.2.0]hexane-like transition state made possible by the relatively long C-S bonds, both existing and incipient (Scheme 3, path a). Alternatively, taking note of the widely accepted stepwise zwitterionic intermediate model for the extrusion of CO 2 from β-lactones, [38][39][40][41][42][43][44][45][46][47][48] it may be considered as arising from trapping of a transient zwitterionic form of the lactone (Scheme 3, path b). While the elucidation of the mechanism of formation of 13 from 4 must await further work, the formation of 13 serves to underline the preference of β-lactones toward nucleophilic ring opening at the β-position by soft nucleophiles [49][50][51][52][53][54][55][56] even though the nucleophile is ideally placed for attack on the carbonyl centre.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the fact that thiolates are well-known to open β-lactones by S N 2 attack at the β-position, this remarkable reaction might be viewed as an intramolecular S N 2-like process involving a bicyclo[2.2.0]hexane-like transition state made possible by the relatively long C-S bonds, both existing and incipient (Scheme 3, path a). Alternatively, taking note of the widely accepted stepwise zwitterionic intermediate model for the extrusion of CO 2 from β-lactones, [38][39][40][41][42][43][44][45][46][47][48] it may be considered as arising from trapping of a transient zwitterionic form of the lactone (Scheme 3, path b). While the elucidation of the mechanism of formation of 13 from 4 must await further work, the formation of 13 serves to underline the preference of β-lactones toward nucleophilic ring opening at the β-position by soft nucleophiles [49][50][51][52][53][54][55][56] even though the nucleophile is ideally placed for attack on the carbonyl centre.…”
Section: Resultsmentioning
confidence: 99%
“…21 This stereoretentive pathway occurred via the formation of a stable zwitterionic intermediate ( − O 2 CCH 2 CR 2 + ) featuring a carboxylate anion and a tertiary carbocation. 22 However, 2,3-disubstituted epoxides would result in the formation of a secondary carbocation, which would produce a less stable zwitterion. To determine whether pathway 1 was feasible, β-butyrolactone, which would also afford a secondary carbocation, was subjected to deoxygenation conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To narrow down possible reaction mechanisms, we drew upon our knowledge of Lewis acid-mediated, lactone decarboxylation reactions (Scheme , pathway 1), which we previously observed during the carbonylation of 2,2-disubstituted epoxides . This stereoretentive pathway occurred via the formation of a stable zwitterionic intermediate ( − O 2 CCH 2 CR 2 + ) featuring a carboxylate anion and a tertiary carbocation . However, 2,3-disubstituted epoxides would result in the formation of a secondary carbocation, which would produce a less stable zwitterion.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of β‐lactone 4k with diethylaluminum ethoxide or dimethylaluminum chloride led to a mixture of β‐lactone, β‐hydroxy ester and olefin (Scheme ). Decarboxylation occurs with aryl derivatives because of the electron density of the aryl group: it was actually demonstrated that electron‐rich groups at the C‐4 position of 2‐oxetanones facilitate the decarboxylation reaction 2a,18. Finally, the mechanism probably involves a stepwise fragmentation through a zwitterionic intermediate because both β‐lactone fragmentations are nonstereoselective.…”
Section: Resultsmentioning
confidence: 99%